The Experience of Living with Diabetes Mellitus during the Covid-19 Pandemic: A Systematic Review of Qualitative Studies - Thongtaeng, Pulawit; Seesawang, Junjira (Nursing Science Journal of Thailand, 2023)
Purpose: To identify and synthesize the experiences of people with diabetes mellitus during the COVID-19 pandemic. Design: A qualitative systematic review following PRISMA guideline. Methods: A search for qualitative studies published in English between December 2019 and June 2022 was conducted using PubMed, CINAHL, PsycInfo, Web of Science, Cochrane Central, Google Scholar databases. Eight qualitative studies were included in this review. Thematic analysis was used to analyze and synthesize findings from qualitative studies based on Thomas and Harden’s steps. Main findings: The literature described the experiences of diabetic patients during COVID-19 pandemic in six themes: (1) perception toward COVID-19, (2) advantage in diabetes management, (3) psychosocial burden, (4) disrupted diabetes management, (5) getting healthier, and (6) guidance needs. Conclusion and recommendations: The literature reviewed suggests that patients with diabetes faced with disrupted self-management and adaption to new diabetes routines. Accessibility of healthcare providers for personalized advice should be provided to support suitable diabetes self-management. Nurse should create interventions to provide information and to mitigate negative emotions and improve coping in patients with diabetes. How best to tailor nursing interventions to support patients with diabetes to perform diabetes self-management in COVID-19 pandemic should be explored.